An Empirical Study of System Improvement by Frontline Employees in Hospital Units - Tucker, Anita L. (Manufacturing and Service Operations Management, 2007)
This paper investigates the conditions under which frontline employees take initiative to improve their work systems to prevent operational failures. Drawing on the system improvement and team learning literatures, we develop a framework of frontline system improvement and test it using survey data from 37 workgroups. We find that psychological safety—the belief that one can talk about errors without risk of punishment—and problem-solving efficacy—the belief that the organization will support employees' system improvement efforts—were positively correlated with frontline system improvement (FLSI). Surprisingly, felt responsibility was negatively associated with FLSI. These findings suggest that rather than relying on hiring motivated individuals, managers need to support employees' efforts to improve their work systems by creating a work environment where it is safe to talk about operational failures and responding to employee communication about operational failures. Doing this may result in higher levels of FLSI efforts and ultimately improve work processes.